2020
DOI: 10.2196/24514
|View full text |Cite
|
Sign up to set email alerts
|

Research Output and International Cooperation Among Countries During the COVID-19 Pandemic: Scientometric Analysis

Abstract: Background The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has instigated immediate and massive worldwide research efforts. Rapid publication of research data may be desirable but also carries the risk of quality loss. Objective This analysis aimed to correlate the severity of the COVID-19 outbreak with its related scientific output per country. Methods All articles related to the COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
3
20
1
Order By: Relevance
“…Satisfactory time for peer-review processes must be maintained even in high rank journals [37]. We found that Chinese authors were mostly cited.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Satisfactory time for peer-review processes must be maintained even in high rank journals [37]. We found that Chinese authors were mostly cited.…”
Section: Discussionmentioning
confidence: 87%
“…In this period, it was reported that time Indeed, the turnover time from submission to acceptance reduced by 49% [42]. Moreover, Some manuscripts were actually accepted on the day of submission [37]. Inevitable consequence of this rush is loss of quality and mistakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of COVID-19 pandemic, many research communities and agencies dedicated their efforts to fight against this infectious disease with their own resources and means. One of these efforts was the sharing of coronavirus-related scientific research as openly as possible (Colavizza et al 2021 ; Grammes et al 2020 ; Tornberg et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 editorial materials in the beginning stage of the pandemic were analyzed (López-López et al, 2021). The patterns of international collaboration on COVID-19 (Duan & Xia, 2021;Grammes et al, 2020) were studies. COVID-19 pandemic-related research in Africa (Fonkou et al, 2021), in Iran (Shamsi et al, 2020), and in the Latin American contributions (Gregorio-Chaviano et al, 2020) were also reported.…”
mentioning
confidence: 99%